A comparative analysis of the impact of the COVID-19 pandemic on rural university students in South Africa and Uganda - Newlin, Marongwe; Loyce, Kobusingye Kiiza (Penerbit Universiti Kebangsaan Malaysia, 2022)
The outbreak of COVID-19 significantly caused shifts in higher education’s environment and operational norms. This has propelled new educational strategies, models and frameworks. Globally, COVID-19 wreaked havoc on institutions of higher learning, such as universities. This was a qualitative comparative and phenomenological study aimed at exploring the impact and implications of COVID-19 on rural university students in South Africa and Uganda. The services offered to rural communities have a bearing on educational institutions in those environments. The study further suggested possible contingency plans to counter the negative impacts caused by such pandemics on rural students in universities. The findings, through a thematic analysis, revealed that rural university students in the two countries were affected by COVID-19 instructional, psychological and social ways. In conclusion, rural university students have peculiar challenges due to their unique but disadvantaged settings. The study recommends that online teaching and learning be prioritized to benefit rural students, preceded by adequate training in Ed Tech skills for both lecturers and students. There is need for guidance and counselling psycho-social interventions for rural university students to address the related challenges.